Political Landscapes of Capital Cities - Christie, Jessica Joyce; Bogdanovic, Jelena; Guzmán, Eulogio (University Press of Colorado, 2016)
"[Political Landscapes of Capital Cities] is a welcome contribution to the study of the spatialization of society and suggests paths that anthropologists can take to analyze political space in urban and non-urban settings alike." -Anthropology Review Database"[O]utstanding contributions of an interdisciplinary group of authors trained in different methodologies. . . . offer[s] both scholarly and popular audiences wide-ranging perspectives in exploring, imagining, perceiving and experiencing capital cities." -Journal of Urban Cultural Studies